Identification of Eimeria Spp. on Commercial Broiler Chicken Farms in the Western Region of the State of Santa Catarina, Brazil, Using Next-Generation Sequencing - Beretta, B. M.S. [UNESP]; Itoyama, B. F. [UNESP]; Hossotani, C. M.S. [UNESP]; Silva, D. R.R. [UNESP]; Garcia Neto, M. [UNESP]; Lopes, F. L. [UNESP]; Dumalakas, G. Z. [UNESP]; Meireles, Marcelo V. [UNESP] (FapUNIFESP (SciELO), 2024)
This study aimed to determine the prevalence of Eimeria spp., including the recently described Eimeria species Eimeria lata, Eimeria nagambie, and Eimeria zaria, on commercial broiler chicken farms (CBCFs) in the western region of the state of Santa Catarina, and to correlate their prevalence with the anticoccidial programs. Ninety-six fecal samples corresponding to 96 commercial broiler farms were examined by microscopic screening and genus-specific PCR (ITS-1 gene). All positive samples were subjected to genus-specific nested PCR (18S rRNA gene), followed by next-generation sequencing to identify the Eimeria species, and new Eimeria operational taxonomic units. Eimeria spp. were identified in 80.2% (77/96) of the samples. Next-generation sequencing revealed the following order of prevalence: Eimeria acervulina (70/77; 90.9%), Eimeria maxima (65/77; 84.4%), Eimeria mitis/mivati (17/77; 22.1%), and Eimeria praecox (37/77; 48.1%). Eimeria spp. were identified on 100% (62/62) and 44% (15/34) of the CBCFs employing treatment with salinomycin and nicarbazin, respectively. In conclusion, we observed a greater prevalence of Eimeria acervulina and Eimeria maxima; a lower prevalence of Eimeria mitis and Eimeria praecox; and the absence of Eimeria brunetti, Eimeria lata, Eimeria nagambie, Eimeria necatrix/tenella, and Eimeria zaria. There was lower positivity for Eimeria spp. on CBCFs employing treatment with nicarbazin.
Keywords: Coccidiosis; Molecular diagnosis; Next-generation sequencing; Poultry